Contents of Secondary Metabolite Compounds in Herbal Tea Combination of Telang (Clitoria ternatea L.). and Holy Basil (Ocimum sanctum L.) - Sabilla Khautsar Andesa; Supriatno Supriatno; Hafnati Hafnati (Universitas Syiah Kuala, 2020)
Plants used as herbal tea as holy basil (Ocimum sanctum L.) and telang (Clitoria ternatea L.) which are thought to contain secondary metabolites and have potential as antioxidants. The purpose of this research was to determine the components of secondary metabolites. This research is an experimental research with a qualitative approach. Secondary metabolite compound tests carried out include flavonoids, alkaloids, terpenoids, tannins and saponin tests. Each test for the content of secondary metabolites used a specific reagent capable of detecting the content in the sample. There is a content of secondary metabolite components (flavonoids, alkaloids, terpenoids, and saponins) and negative results for tannins. The presence of these secondary metabolites indicates that the combination herbal tea has potential as an antioxidant.